EDUCATIONAL SYSTEM FOR THE DEVELOPMENT OF CREATIVE SKILLS OF UPPER-CLASS STUDENTS IN THE PROCESS OF OUT-OF-CURRICULUM STUDIES OF HISTORICAL AND CULTURAL MONUMENTS OF UZBEKISTAN - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi, (Журнал иностранных языков и лингвистики, 2023)
In the procedural and pedagogical system, the structural basis of a given process, stepwise structural elements (subsystems) with a given organization represent certain levels, primarily information, and management. In our practice of developing creative abilities, in extracurricular activities, the processual pedagogical system of high school students is a structural and meaningful basis, in which the following components are highlighted: motivating, organization-installing, personality-oriented, specific, vocabulary-conceptual, information-cognitive, reflexive - intellectual-creative, creative activity, self-improvement, self-realization and socialization, objective self-esteem.